ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERN TERHADAP KINERJA DAN PENERIMAAN RETRIBUSI PARKIR DI DINAS PERHUBUNGAN KOTA MANADO - Munaiseche, Claudio V.; Ilat, Ventje; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Internal control systems are needed for every government agency from planning, supervision, to accountability, must be carried out in an orderly, controlled, efficient and effective. So that the performance of government agencies is directed and reaches the goal. This study aims to determine whether the implementation of the internal control system on the performance and retribution parking income at the Manado city transportation office is adequate or inadequate. This research method is a qualitative descriptive study. Based on the results of the research and discussion, it can be seen that the internal control system on the performance and retributionÂ  parking income at Transportation department of at Manado city has been "adequate and effective" because the procedure for retribution parking income have elements of internal control, namely the proper delegation of authority and responsibility. the separation of functions, recording carried out accurately and on time, the documents used contain clear and reliable information and are carried out continuously. The target achievement of the 2016-2017Â  is effective and the performance had been in accordance with government regulation number 60 of 2008 concerning the government's internal control system.Keywords: Government Internal Control System, Performance, Income Parking Retribution